Risk Management for Whole-Process Safe Disposal of Medical Waste: Progress and Challenges - Yang T; Du Y; Sun M; Meng J; Li Y (Risk Management and Healthcare Policy, 2024)
Ting Yang,1,2 Yanan Du,1 Mingzhen Sun,1 Jingjing Meng,1 Yiyi Li1 1School of Health Services Management, Anhui Medical University, Hefei, Anhui, 230032, People’s Republic of China; 2Intelligent Interconnected Systems Laboratory of Anhui Province (Hefei University of Technology), Hefei, Anhui, 230009, People’s Republic of ChinaCorrespondence: Ting Yang, Email yangting@ahmu.edu.cnAbstract: Over the past decade, the global outbreaks of SARS, influenza A (H1N1), COVID-19, and other major infectious diseases have exposed the insufficient capacity for emergency disposal of medical waste in numerous countries and regions. Particularly during epidemics of major infectious diseases, medical waste exhibits new characteristics such as accelerated growth rate, heightened risk level, and more stringent disposal requirements. Consequently, there is an urgent need for advanced theoretical approaches that can perceive, predict, evaluate, and control risks associated with safe disposal throughout the entire process in a timely, accurate, efficient, and comprehensive manner. This article provides a systematic review of relevant research on collection, storage, transportation, and disposal of medical waste throughout its entirety to illustrate the current state of safe disposal practices. Building upon this foundation and leveraging emerging information technologies like Internet of Things (IoT), cloud computing, big data analytics, and artificial intelligence (AI), we deeply contemplate future research directions with an aim to minimize risks across all stages of medical waste disposal while offering valuable references and decision support to further advance safe disposal practices.Keywords: medical waste, safe disposal, major infectious diseases, progress and challenges